2(x+1)+5x=3(x+1)-2

Simple and best practice solution for 2(x+1)+5x=3(x+1)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+1)+5x=3(x+1)-2 equation:


Simplifying
2(x + 1) + 5x = 3(x + 1) + -2

Reorder the terms:
2(1 + x) + 5x = 3(x + 1) + -2
(1 * 2 + x * 2) + 5x = 3(x + 1) + -2
(2 + 2x) + 5x = 3(x + 1) + -2

Combine like terms: 2x + 5x = 7x
2 + 7x = 3(x + 1) + -2

Reorder the terms:
2 + 7x = 3(1 + x) + -2
2 + 7x = (1 * 3 + x * 3) + -2
2 + 7x = (3 + 3x) + -2

Reorder the terms:
2 + 7x = 3 + -2 + 3x

Combine like terms: 3 + -2 = 1
2 + 7x = 1 + 3x

Solving
2 + 7x = 1 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
2 + 7x + -3x = 1 + 3x + -3x

Combine like terms: 7x + -3x = 4x
2 + 4x = 1 + 3x + -3x

Combine like terms: 3x + -3x = 0
2 + 4x = 1 + 0
2 + 4x = 1

Add '-2' to each side of the equation.
2 + -2 + 4x = 1 + -2

Combine like terms: 2 + -2 = 0
0 + 4x = 1 + -2
4x = 1 + -2

Combine like terms: 1 + -2 = -1
4x = -1

Divide each side by '4'.
x = -0.25

Simplifying
x = -0.25

See similar equations:

| x+2(x-6)=-4(x-1) | | 13x+2=11-5 | | 3(y-8)-4=-5(-4y+2)-y | | -10=3m | | x*x*x-3*x*x-3*x-1=0 | | -x/6=3/9 | | -x-12+5x=9-10x+7 | | X+(140-g)+(20+g)+g=290 | | N/-10=3 | | 7u+47=3(u+9) | | X/3=1.8 | | 9-7=8 | | 3x-2(x-5)=7x-4(2x+1) | | 35x-5=x+17 | | -x/6=6/9 | | 5(w-2)-7w=-30 | | x^2-8x+13=-4 | | 2x^7+18x^6+36x^5=0 | | X+22=35x | | 18+19m+m^2=0 | | 1/0*190340 | | -3/8=x/24 | | r^2-6r-83=-10 | | -3n+12-n=40+8 | | 7/10-7=7 | | X/10=7/10 | | v^2-12v+34=-6 | | 2+6x-2x=-8+2x | | A^4-2a^2-35=0 | | 2x+3=3x+-2 | | 81r^2-49= | | 17=kg-2 |

Equations solver categories